SISTEM INFORMASI PENJUALAN BATIK BERBASIS WEB PADA TOKO KAFAYA BATIK BEKASI - Aulianita, Rizki; Herlawati, Herlawati; Santoso, Budi (LPPM Universitas Nusa Mandiri, 2013)
Developments in information technology are rapidly evolving, making information easy to obtain and disseminated. Opportunities that are seen by the market authorities or employers to utilize Internet technology in running its business primarily by using the website. The website is one of the most widely used alternatives to expanding access or business coverage, not limited by time and space requirements must be connected to the internet. Shop Kafaya Batik Bekasi engaged in the sale of original batik Pekalongan still use a conventional or manual to make transactions. To reach the international market, without having to meet face to face or directly with the customer and the operational costs are not small, the author gives an idea or ideas to create e-commerce website selling batik in hopes of helping to expand to expand the market. Moreover Batik cultural heritage as a noble nation that has been recognized by UNESCO to be one of our heritage to remain preserved and developed not only in Indonesia but can also include worldwide markets overseas or abroad.